Labour market expectations and occupational choice: Evidence from teaching - Joshua Fullard (University of Essex, Institute for Social and Economic Research (ISER), 2023)
Using new data on teachers' intentions to leave the profession, subjective expectations about labour market outcomes and a modified discrete-choice experiment we find that i) teachers are systematically misinformed about population earnings, and misinformation is correlated with attrition intentions; ii) non-pecuniary factors are the most cost-effective method of reducing teacher attrition; and iii) attrition intentions are more affected by reductions in workplace amenities than symmetric improvements, suggesting preventing cuts is more important that rolling out more generous benefits. Linking our survey data to teachers' administrative records we provide the first evidence that teachers attrition intentions are strong predictors of actual behaviour.
Keywords: I20; J30; J45; C90; 330; teacher labour markets; subjective expectations